2018
DOI: 10.3389/fpls.2018.00999
|View full text |Cite
|
Sign up to set email alerts
|

Application of Controlled-Release Urea Enhances Grain Yield and Nitrogen Use Efficiency in Irrigated Rice in the Yangtze River Basin, China

Abstract: The use of controlled-release urea (CRU) has been recommended over that of conventional urea to improve rice grain yield and nitrogen use efficiency. However, the underlying agronomical and physiological mechanisms need to be better understood. In this study, field trials over four site-years, and a big container experiment were carried out to explore CRU effects on rice yield and NUE, with the main aims to identify the key yield components contributing to the superior rice yield with CRU use, and to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 50 publications
(80 reference statements)
3
39
0
Order By: Relevance
“…Some studies have suggested that increasing dry matter accumulation before flowering has an important effect on grain yield (Pal, Mahajan, Sardana, & Chauhan, 2017;Wu et al, 2013). Increasing evidence has shown that dry matter accumulation post-anthesis is important in determining grain yield in rice (Li, Wei, Xu, Wang, & Xu, 2016;Mahajan & Chauhan, 2016;Wang, Xue, Pan, Chen, & Liu, 2018;Wei et al, 2018). Although the relationship among dry matter, photosynthetic production, and rice yield has been studied (Amanullah & Inamullah, 2016;Chen, Zhang, Zhang, Wang, & Xu, 2012), the effects of integrated crop management practices on these parameters still need to be elucidated.…”
Section: Crop Sciencementioning
confidence: 99%
“…Some studies have suggested that increasing dry matter accumulation before flowering has an important effect on grain yield (Pal, Mahajan, Sardana, & Chauhan, 2017;Wu et al, 2013). Increasing evidence has shown that dry matter accumulation post-anthesis is important in determining grain yield in rice (Li, Wei, Xu, Wang, & Xu, 2016;Mahajan & Chauhan, 2016;Wang, Xue, Pan, Chen, & Liu, 2018;Wei et al, 2018). Although the relationship among dry matter, photosynthetic production, and rice yield has been studied (Amanullah & Inamullah, 2016;Chen, Zhang, Zhang, Wang, & Xu, 2012), the effects of integrated crop management practices on these parameters still need to be elucidated.…”
Section: Crop Sciencementioning
confidence: 99%
“…In addition, SRCF+U and CF+SCU significantly increased the nutrient utilization efficiency compared with the 100% conventional chemical N fertilizer treatment. A previous study reported that slow-release fertilizers reduced the fertilizer N losses (Xu et al, 2012), which therefore enhanced the nutrient utilization efficiency compared with the conventional N fertilizers (Kiran et al, 2010;Ye et al, 2013;Wang et al, 2015Wang et al, , 2018. Furthermore, the nutrient uptake and utilization efficiency for SRCF+U were higher than for CF+SCU.…”
Section: N P and K Absorption And Utilization Efficiency For The Difmentioning
confidence: 94%
“…Similar to organic fertilizers, slow-release fertilizers are designed to release the fertilizer into the soil at a rate that meets the nutritious requirement of the rice plants compared with conventional chemical fertilizers (Wang et al, 2011(Wang et al, , 2018Zheng et al, 2016). Therefore, it could save chemical fertilizer and enhance nutrient utilization efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Soybean is an economically important crop that is grown worldwide for the high contents of oil (20–25%) and protein (42–45%) in its seeds (Adak and Kibritci, 2016). Although soybean is extremely important for human consumption, it has a lower yield than other important food crops, such as wheat, rice, and maize (Wen et al, 2016; Gao et al, 2018; Ma et al, 2018). Although a three-line system based on CMS has been developed in soybean, large-scale hybrid seed production is difficult to achieve because of the extremely low frequency of natural cross-pollination (Ray et al, 2003).…”
Section: Introductionmentioning
confidence: 99%